STRATEGI PEMASARAN INDUSTRI DAN BISNIS - Panigoro, Tri; Asep, Dimas Adetiya; Gunawan, Yoga (Expectation: Journal of Islamic Education Management, 2025)
In recent decades, industrial and business development has become a major pillar of the global economy, driven by the Industrial Revolution 4.0 and globalization. This article utilizes a qualitative method with library research, and the data itself is processed using descriptive analysis. This article discusses the basic concepts of marketing, the objectives, and functions of marketing strategy. An effective marketing strategy is crucial in a competitive business environment, enabling companies to differentiate themselves from competitors and attract consumers. Furthermore, the article discusses the Six Sigma method in business, a data-driven approach to improving process performance by eliminating defects. The DMAIC (Define, Measure, Analyze, Improve, Control) methodology is used to identify, analyze, and correct problems in business processes. Through the integration of effective marketing strategies and the implementation of Six Sigma, companies can gain a sustainable competitive advantage in a dynamic marketplace.